Patterns of Antiretroviral Therapy Use and Immunologic Profiles at Enrollment in the REPRIEVE Trial. (9th July 2020) - Fichtenbaum, Carl J; Ribaudo, Heather J; Leon-Cruz, Jorge; Overton, Edgar T; Zanni, Markella V; Malvestutto, Carlos D; Aberg, Judith A; Kileel, Emma M; Fitch, Kathleen V; Van Schalkwyk, Marije; Kumarasamy, Nagalingeswaran; Martinez, Esteban; et al.
Abstract: Background: Patterns of antiretroviral therapy (ART) use and immunologic correlates vary globally, and contemporary trends are not well described. Methods: The REPRIEVE trial (Randomized Trial to Prevent Vascular Events in HIV) enrolled persons with human immunodeficiency virus (HIV) who were aged 40–75 years, receiving ART, and had low-to-moderate cardiovascular disease risk. ART use was summarized within Global Burden of Disease (GBD) super-regions, with adjusted linear and logistic regression analyses examining associations with immune parameters and key demographics. Results: A total of 7770 participants were enrolled, with a median age of 50 years (interquartile range, 45–55 years); 31% were female, 43% were black or African American, 15% were Asian, 56% had a body mass index >25 (calculated as weight in kilograms divided by height in meters squared), and 49% were current or former smokers. The median CD4 T-cell count was 620/µL (interquartile range, 447–826/ µ L), and the median duration of prior ART use, 9.5 years (5.3–14.8) years. The most common ART regimens were nucleoside/nucleotide reverse-transcriptase inhibitor (NRTI) plus nonnucleoside reverse-transcriptase inhibitor (43%), NRTI plus integrase strand transfer inhibitor (25%), and NRTI plus protease inhibitor (19%). Entry ART varied by GBD region, with shifts during the trial enrollment period. In adjusted analyses, entry CD4 cell count and CD4/CD8 ratio were associated with GBD region, sex, entry regimen, duration of ART, and nadir CD4 cell count; CD4 and CD8 cell counts were also associated with body mass index and smoking status. Conclusions: There were substantial variations in ART use by geographic region and over time, likely reflecting the local availability of specific medications, changes in treatment guidelines and provider/patient preferences. The analyses of CD4 cell counts and CD4/CD8 ratios may provide valuable insights regarding immune correlates and outcomes in people living with HIV. Clinical Trials Registration: NCT02344290.